Construction of an adaptive river-based recreational network for urban river restoration: A case study of Rencheng District, Jining City, China. (10th November 2022) - Zheng, Xin; Wang, Fuyuan
Abstract: Recreation-oriented urban river ecological restoration can help restore damaged ecosystems and improve human well-being. This study selects the urban river network of Rencheng District, Jining City, China as a case to map and construct a river-based recreational network (RRN) in an urban river restoration context. Morphological spatial pattern analysis, connectivity evaluation methods, and an overlay method of ArcGIS are applied to identify river network connectivity and ecological sources, which are used to map RRN. The research findings show that except rivers in the Liangshan-Jining Canal, other rivers have medium, poor, or extremely poor ecological connectivity. The ecological sources are mainly distributed in the vicinity of Nanyang lake and Taibai lake. The distribution of river connectivity is largely correlated with the regional physical geography pattern (e.g., geological structure and topological position of water patches), as well as historical human activities (e.g., canalization). Furthermore, the continuous subsidence of coal mining subsidence areas, urban expansion and rural construction, environmental damage and pollution, natural changes (e.g., climate change) are the risk sources of river network connectivity. To restore the ecological and social connectivity of urban river network, an adaptive RRN is proposed according to the current environmental status and the factors affecting the river connectivity. Specifically, form-based and process-based restoration measures can be adopted in urban built-up areas and rural areas, respectively. The findings provide a holistic solution for the restoration and recreational use of urban river network at a regional scale, thereby promoting the coordination of urban ecosystems and sociocultural systems.